Localizing English literature as a school subject: a Malaysian experience - Lim, Jia Wei (Taylor & Francis, 2018)
This article explores some of the complexities involved in the act of localizing English literature as a school subject. Informed by Goodson and Marsh’s stages of subject development, I explore the ways in which post-16 English literature was localized in Malaysia from an introduced and mythologized subject entitled “English” to its reconceptualization as “Literature in English” in the year 1998. The main question this article asks is: can a mythologized subject be sustained when it is introduced into another context (i.e., Malaysia)? This question is explored through attempts made to localize it by the subject’s governing body in Malaysia, namely the Malaysian Examinations Council. Relevant documents as well as an interview with a subject committee member involved in the subject’s reconceptualization form the data of this article. Analysis suggests that not only were acts of localization incoherent in the subject’s implementation, the rationale for localization was also not shared by some constituencies within and beyond the education system. This article concludes by highlighting the importance of ensuring that support from relevant constituencies is based upon a shared understanding of a subject’s role, aims and conceptualization in order to sustain subject development in an education system.